Evaluation of the Nipah epidemic containment and multisectoral involvement in Kerala using an appropriate management framework - Rahim, Asma A.; Muthukutty, Sujina C.; Jacob, Sabitha R.; Ravindran, Rini; Thayyil, Jayakrishnan; Thavody, Jayakrishnan (International Journal Of Community Medicine And Public Health, 2020)
Kozhikode district of North Kerala, India witnessed an outbreak of Nipah virus (NiV) in the month of May 2018. Two adjacent districts were affected leaving 17 patients dead out of the 19 confirmed. United Nations and WHO lauded the expeditious response of the state’s health system in the diagnosis and containment of the outbreak which was unprecedented. The authors being in the contact tracing and surveillance operation district team, had kept a record of timeline of events and actions at the state level, compiled the news clippings and tracked events. In the absence of an end‑of‑epidemic report for reference, these records served as a valuable tool for the present review. We used the Management science for health frame work tool (MSH framework) to evaluate the district and state coordinated actions which helped in curbing the outbreak. Though NiV outbreak in South India (2018) had similar epidemiological features to previous disease outbreaks, it stands out as the one to be detected and contained in a short span of time. As health personnel working in the government medical college of an affected district and directly involved in contact tracing operations and containment measures, exploring and sharing, what worked and how, in the context of multidisciplinary response and recovery attempts of the outbreak in the state may be beneficial to public health personnel and policy makers. This management framework may be replicated in the national and international context, particularly in South East Asian region under threat of emerging viral infections like COVID-19, lacking specific epidemic management frameworks for outbreak response and containment.